The Effect of Internal Audit on the Financial Performance of Commercial Banks: A Case Study of Equity Bank Mukono Branch - Acio Rebecca Mitchelle (Uganda Christian University, 2024)
This study looked at how internal audits affected the financial performance of commercial banks, with a focus on Equity Bank Uganda Ltd, Mukono branch. The research aimed shading light on how different types of internal audits - risk management, compliance, and operational audits - have impacted on the bank's financial performance metrics. In particular, the study’s aim was to: - Figure out how risk management audits affected financial performance Understand how compliance audits helped to improve financial performance - Examine how operational audits contributed to financial performance. The research looked at 50 workers from Equity Bank's Mukono branch. From this group, the researcher chose 40 people who took part, based on Krejcie and Morgan's guide for picking sample sizes. To get information, the researcher used two main ways. First, the researcher talked to people, sent out surveys, and asked them to fill out forms. Second, the researcher looked at old reports online journals, and other published work. The main tool to collect data was a planned set of questions. This questionnaire aimed at understanding what people thought about how well the different types of audits worked. The results showed that risk management audits played a big part in boosting financial performance. They did this by helping to spot and reduce risks, which supported smart decision-making. People saw compliance audits as key to sticking to regulatory rules, which helped increase profits and improved financial reports. Operational audits were thought to be useful for better budgeting and financial planning. However, respondents’ views differed on how much they helped with using resources and increasing overall profits. Suggestions involved using a clear plan for handling risks, making sure that checks for following rules matched what the rules said, and improving how operations were checked to deal with different views. Spending on better tools, training, and encouraging honest talks between those who checked and those who were in charge was suggested to make internal checks work better and help the bank do better financially. The researcher offered useful ideas for banks wanting to make their internal check-ups better and their financial results stronger.